Heterogeneity, High Performance Computing, Self-Organization and the Cloud - Lynn, Theo.; Morrison, John P.; Kenny, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2018)
This open access book addresses the most recent developments in cloud computing such as HPC in the Cloud, heterogeneous cloud, self-organising and self-management, and discusses the business implications of cloud computing adoption. Establishing the need for a new architecture for cloud computing, it discusses a novel cloud management and delivery architecture based on the principles of self-organisation and self-management. This focus shifts the deployment and optimisation effort from the consumer to the software stack running on the cloud infrastructure. It also outlines validation challenges and introduces a novel generalised extensible simulation framework to illustrate the effectiveness, performance and scalability of self-organising and self-managing delivery models on hyperscale cloud infrastructures. It concludes with a number of potential use cases for self-organising, self-managing clouds and the impact on those businesses.
1 Addressing the Complexity of HPC in the Cloud: Emergence, Self-Organisation, Self-Management and the Separation of Concerns -- 2 Cloud Architectures and Management Approaches -- 3 Self-organising, Self-Managing Frameworks and Strategies -- 4 Application Blueprints and Service Description -- Simulating Heterogeneous Clouds at Scale -- Concluding Remarks.
Keywords: Quantitative research; Business logistics; Industries; Electronic data processing -- Management; Computer systems; Data Analysis and Big Data; Logistics; Industries; IT Operations; Computer System Implementation